Vietnam-Japan Higher Education Cooperation in the First Two Decades of the 21st Century - Nguyen Thi, Thanh Tu (WILAYAH: The International Journal of East Asian Studies, 2022)
Since diplomatic relations between Vietnam and Japan were officially established in September 1973, the relationship between the two countries has increasingly expanded and achieved outstanding achievements in many aspects of economy, socio-culture, science and technology, especially in the fields of education and training. At the higher education level, the two governments have been promoting cooperation programs and projects such as transnational education, exchange of students and lecturers. Additionally, every year, Japan offers more than one hundred scholarships to Vietnamese undergraduate, graduate, and doctoral students to study and research in Japan. These projects have significantly contributed to improving the quality of Vietnam’s higher education, helping Vietnam to train high-quality human resources for the country’s industrialization and modernization. In order to further stimulate higher education cooperation between the two countries, however, it is necessary to examine what has been accomplished so far and what problems remain, so as to propose recommendations that might enhance education cooperation between Vietnam and Japan in the coming years. The objective of this study is to briefly introduce the basis of higher education cooperation between Vietnam and Japan. It also seeks to analyze and assess the current situation and policy as well as achievements and challenges of higher education cooperation between the two countries over the past 20 years. Thenceforth, it proposes a number of recommendations for further strengthening higher education cooperation between Vietnam and Japan in the coming years.